Pengaruh Fitur Desain dan Bahasa Terhadap Kepuasan User dalam Proses Belajar Mengajar Pada Universitas di Jakarta - Lianawati Christian; Angelina Permatasari; Lianna Sugandi (Bina Nusantara University, 2014)
This research was conducted at the research object that is engaged in educational services is one of the universities in Jakarta, where do research on features or design variables and the variable satisfaction language on the web that support the teaching and learning process at the college. The purpose of this study was to determine the factors that affect the learning process on the web, as reference material consideration for the leadership of the university in the policy -making to improve the quality quality teaching and learning process. The method used is literature and literature study, questionnaires to the users who use the web are faculty and students, interviews, data processing method with SPSS and Likert scale. The conclusions resulting from this research is the design and navigation of the questionnaire distributed to faculty and students in the first semesterof 2013/2014 with the hypothesis Ho: no effect, Ha: no effect, in which the basic decision making sig. > then Ho isα= accepted , sig . < then Ho is rejected, the decision sig. = 0.00 then 0.00α < 0.05 then there is the influence of language and design variable to variable satisfaction.